2019
DOI: 10.5327/z1414-4425201900020007
|View full text |Cite
|
Sign up to set email alerts
|

Uso do ultrassom portátil para detecção de retenção urinária por enfermeiros na recuperação anestésica

Abstract: Objetivo: Verificar a opinião dos enfermeiros em relação à utilização do ultrassom portátil para detectar retenção urinária na recuperação anestésica. Método: Pesquisa de campo, descritivo-exploratória, quantitativa; com 34 enfermeiros de dois blocos cirúrgicos de um hospital privado de São Paulo; aplicado questionário com duas partes: caracterização do profissional e questões sobre o uso do ultrassom portátil. A coleta deu-se entre maio e junho de 2018, após cumpridas as recomendações da Resolução nº 466/2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
32

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 12 publications
0
14
0
32
Order By: Relevance
“…Although US has shown to be a useful diagnostic resource to identify urinary volume, a better understanding on UR lacks the establishment of parameters (urinary values) that clearly define UR, which is not still a consensus in the literature (4,17) . Nevertheless, it is perceived that methods employed for the identification of UR that involve greater subjectivity may disagree among each other, in the absence of objective parameters, not contributing with nurses in deciding on whether to perform BRC or not (12) . This lack of criteria to diagnose UR and, therefore, to indicate BRC, contributes to the great variability in the incidence rates of UR described in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although US has shown to be a useful diagnostic resource to identify urinary volume, a better understanding on UR lacks the establishment of parameters (urinary values) that clearly define UR, which is not still a consensus in the literature (4,17) . Nevertheless, it is perceived that methods employed for the identification of UR that involve greater subjectivity may disagree among each other, in the absence of objective parameters, not contributing with nurses in deciding on whether to perform BRC or not (12) . This lack of criteria to diagnose UR and, therefore, to indicate BRC, contributes to the great variability in the incidence rates of UR described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the identification of urinary volume by ultrasound (US) has been tested, showing to be a useful diagnostic method for the detection of UR at the bedside (12) . Furthermore, a research study found a strong correlation between the urinary volume estimated by US and the one drained from urinary catheterization (11) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em estudo realizado por Carnaval et al, (2019), esplana que por se tratar de um equipamento incomum na prática da assistência de enfermagem, são necessários treinamentos teórico-práticos para o acesso a todos os recursos do dispositivo e, principalmente em programas de graduação e pós-graduação, além da criação de protocolos institucionais, e treinamentos constantes para equipe.…”
Section: )unclassified
“…Técnicas de imagem são complementares ao exame físico e favorecem com acurácia diagnóstica o trabalho do enfermeiro (Bastos, Silveira Vieira & Muniz Pazeli, 2019) Entre os métodos de imagens disponíveis a ultrassonografia (USG) é bem aceita e incorporada às diversas áreas da saúde, por ser um recurso não invasivo, compacto e de baixo custo (Carnaval, Teixeira & Carvalho, 2019) Embora a premência e relevância do tema, não são identificadas revisões existentes relacionadas ao tópico de interesse nas principais bases de registros de protocolos International prospective register of systematic reviews -PROSPERO, US National Library of Medicine (Medline), Cumulative Index to Nursing and Allied Health (CINHAL), Cochrane Database of Systematic Reviews e JBI Database of Systematic Reviews and Implementation Reports) reforçando a lacuna sobre o tema. Então, decidiu-se por fazer uma revisão com o identificar na literatura científica aplicações para o uso da ultrassonografia por enfermeiros no bloco operatório.…”
Section: Introductionunclassified